2014
DOI: 10.1016/j.ajpath.2014.05.016
|View full text |Cite
|
Sign up to set email alerts
|

A Desmoplakin Point Mutation with Enhanced Keratin Association Ameliorates Pemphigus Vulgaris Autoantibody-Mediated Loss of Cell Cohesion

Abstract: Desmoplakin (DP) serves to anchor intermediate filaments in desmosomal complexes. Recent data suggest that a specific DP point mutation (S2849G) exhibits increased keratin filament association and fosters Ca(2+) insensitivity of desmosomes in keratinocytes, presumably by rendering DP inaccessible for protein kinase C (PKC) phosphorylation. Previously, we have reported that depletion of the desmosomal adhesion molecule desmoglein (Dsg)3 induced by autoantibodies from patients with the blistering skin disease pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 30 publications
6
34
0
Order By: Relevance
“…It was suggested that primarily the nondesmosomal Dsg3 molecules present on the cell surface and not connected to the keratin filaments sense the initial binding of autoantibodies and relay this signal into the cell, which results in pronounced p38MAPK-dependent Dsg3 depletion (Müller et al, 2008;Spindler and Waschke, 2014;Vielmuth et al, 2015). Furthermore, PKC is activated following a rapid Ca 2+ influx after PV-IgG application (Osada et al, 1997;Rotzer et al, 2014;Seishima et al, 1995) which switches the Ca 2+ -independent, hyperadhesive desmosomes found in fully confluent keratinocytes to a Ca 2+ -dependent phenotype (Cirillo et al, 2010;Dehner et al, 2014). This in turn favors the loss of Dsg3, probably by reorganization of the desmosomal plaque in response to desmoplakin phosphorylation and via mechanisms involving plakophilin-1 Spindler et al, 2011;Tucker et al, 2014).…”
Section: Wounded Keratinocytes Show Remarkable Similarities To Keratimentioning
confidence: 98%
“…It was suggested that primarily the nondesmosomal Dsg3 molecules present on the cell surface and not connected to the keratin filaments sense the initial binding of autoantibodies and relay this signal into the cell, which results in pronounced p38MAPK-dependent Dsg3 depletion (Müller et al, 2008;Spindler and Waschke, 2014;Vielmuth et al, 2015). Furthermore, PKC is activated following a rapid Ca 2+ influx after PV-IgG application (Osada et al, 1997;Rotzer et al, 2014;Seishima et al, 1995) which switches the Ca 2+ -independent, hyperadhesive desmosomes found in fully confluent keratinocytes to a Ca 2+ -dependent phenotype (Cirillo et al, 2010;Dehner et al, 2014). This in turn favors the loss of Dsg3, probably by reorganization of the desmosomal plaque in response to desmoplakin phosphorylation and via mechanisms involving plakophilin-1 Spindler et al, 2011;Tucker et al, 2014).…”
Section: Wounded Keratinocytes Show Remarkable Similarities To Keratimentioning
confidence: 98%
“…Desmoplakin is phosphorylated in the presence of Pemphigus Vulgaris autoimmune antibodies, which decreases cytokeratin intermediate filament binding to desmosomes (Fig. 5; Dehner et al 2014). Thus, all components of desmosomes are required to maintain normal function, and structural integrity of the epidermis.…”
Section: Epidermis Organization and Regulation Of Homeostasismentioning
confidence: 99%
“…1e). Although the applied PV-IgG fraction contains both Dsg3 and Dsg1 autoantibodies, we focused on Dsg3 because under the culture conditions used for this study HaCaTs express Dsg3 but not Dsg1 [14].…”
Section: E-cadherin Compensates For Effects Of Desmosomal Perturbationmentioning
confidence: 99%